Brilliant mindfulness : how the mindful approach can help you towards a better life - Rezek, Cheryl A. (Pearson Education, 2013)
Mindfulness has gained huge support over the past decade and has moved from being an Eastern Buddhist practice to a mainstream Western intervention. This is the most simple and practical guide to the science and practice of mindfulness–a way of being scientifically proven to help reduce stress, improve mood and thinking, and help you cope better with whatever life throws at you. This book gives you what you need to know, quickly and in the most easily absorbed way. The book is illustrated throughout to help you learn the different meditation positions and comes complete with a CD for guided practice.